Poza tekstem: uwagi o filozoficznym tle semiotyki tartuskiej - Łotman, Michaił (Er(r)go. Teoria - Literatura - Kultura, 2015)
Mihhail Lotman Tallinn University, Estonia "Beyond Text: Remarks on the Philosophical Background of Tartu Semiotics" The paper explores various approaches to the concept of text present in the work of Yuri Lotman and the Tartu-Moscow school of semiotics, which is considered here as primarily text oriented. The object of study, however, is not what has been explicitly formulated, but rather what has not been said or what has only been implicated in the work of Lotman and other exponents of the school. In this way the conceptual paradigm of Tartu-Moscow semiotics is placed in the context of (implied) philosophical perspectives.